2016
DOI: 10.18632/oncotarget.11733
|View full text |Cite
|
Sign up to set email alerts
|

DMBA induced mouse mammary tumors display high incidence of activating Pik3caH1047 and loss of function Pten mutations

Abstract: Controversy always existed on the utility of chemically induced mouse mammary carcinogenesis models as valid equivalents for the study of human breast cancer. Here, we performed whole exome and RNA sequencing on long latency mammary tumors (218 ± 27 days) induced by the carcinogen 7,12-Dimethylbenzathracene (DMBA) and short latency tumors (65 ± 11 days) induced by the progestin Medroxyprogesterone Acetate (MPA) plus DMBA in CD2F1 mice. Long latency tumors displayed a high frequency of Pi3kca and/or Pten mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 38 publications
3
45
1
Order By: Relevance
“…These CYP1s metabolize DMBA into free radical intermediates, such as superoxide, hydrogen peroxide, and nitrogen oxide, which could generate a mutagenic DNA adduct through covalent binding to the exocyclic amino groups of purines or the induction of oxidative stress; subsequently, these events induce carcinogenesis . Recently, it was reported that the abrogation of the catalytic subunit of protein phosphatase ( Ppp6c ) accelerated DMBA‐induced tumorigenesis through NF‐κB activation and long‐term exposure to DMBA induced Pik3ca H1047 activation and Pten mutations with loss of function . Although these findings provided clues to the carcinogenic mechanism of DMBA, the detailed mechanism is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These CYP1s metabolize DMBA into free radical intermediates, such as superoxide, hydrogen peroxide, and nitrogen oxide, which could generate a mutagenic DNA adduct through covalent binding to the exocyclic amino groups of purines or the induction of oxidative stress; subsequently, these events induce carcinogenesis . Recently, it was reported that the abrogation of the catalytic subunit of protein phosphatase ( Ppp6c ) accelerated DMBA‐induced tumorigenesis through NF‐κB activation and long‐term exposure to DMBA induced Pik3ca H1047 activation and Pten mutations with loss of function . Although these findings provided clues to the carcinogenic mechanism of DMBA, the detailed mechanism is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Recently, it was reported that the abrogation of the catalytic subunit of protein phosphatase (Ppp6c) accelerated DMBA-induced tumorigenesis through NF-jB activation and long-term exposure to DMBA induced Pik3ca H1047 activation and Pten mutations with loss of function. 33,34 Although these findings provided clues to the carcinogenic mechanism of DMBA, the detailed mechanism is still unknown.…”
mentioning
confidence: 99%
“…Studies have observed main active compounds from terpenoid, such as curzerene, cineole, germacrone, and β-element to exhibit anti-cancer activities towards gastric cancer cell lines. Zhong et al also reported in his study that sesquiterpenoid germacrone exhibited the best anticancer properties by inhibiting cell proliferation, increasing lactate dehydrogenase, and mediating G1 and G2 cell cycle arrest in human breast cancer 10 . Other sesquisterpenes which consist of β, α, and γ-element has also been reported to exhibit anti-tumor activities and approved by the Food and Drug Administration of China as anti-cancer adjuvant drug on cancer patients 8 .…”
Section: Discussionmentioning
confidence: 87%
“…The rhizome of C. aeruginosa is traditionally used for the treatment of gastrointestinal problems, as well as an antimicrobial and anti-inflammatory agent. Other recent studies have also reported this rhizome to possess pharmacological activities for treating various diseases, such as tumor, asthma, and bronchitis [10][11] .…”
Section: Introductionmentioning
confidence: 87%
“…The induction of DMBA and Estradiol carcinogen compounds for 8 weeks induced the formation of breast cancer 7,12-Dimethylbenz[a]anthracene (DMBA) was a carcinogen compound that has an aromatic hydrocarbon chain and has been widely used in research as an inducer in breast cancer modeling [22,23,24]. Estradiol is a steroid the sex hormone that useful in female reproductive cycle in regulation of estrous and menstrual cycles.…”
Section: Resultsmentioning
confidence: 99%